EVALUASI NILAI CUTTING CARRYING INDEX PADA LUMPUR DIESEL OIL - Kevin Ariko Yuwandhika; Bayu Satiyawira; Apriyandi Rizki (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2018)
Evaluation of Cutting Carrying Index when using Diesel Oil base mud in well T is carried out on section 12-1 / 4